The training reform act of 1994 - Layard, R. [Verfasser]; Mayhew, K. [Verfasser]; Owen, G. [Verfasser] (My University, 1993)
"Deplores the paucity of vocational education and training (VET) in the UK, especially for the young, citing economics as a major reason for the deficiencies. Examines the priorities which need to be addressed in expanding the system, arguing or full-time versus part- time training, specialized versus general, adults versus youths, and employer versus self-sponsorship. Disusses training vis-a-vis free tution, traineeship, required attendance, accreditation and administration, and concludes that the UK must policy of often illfunded and chaotic experimentation (in the guise of flexibility), which it has pursued in the last decade, and emergre from the twilight to devise a strategy based on proven international experience." (author's abstract, IAB-Doku) ((en)) Die Autoren vergleichen die Berufsbildungspolitik Grossbritanniens mit anderen europäischen Staaten. (IAB)
Die Reform des Berufsbildungsgesetzes 1994
Keywords: S 1 Stufen der Berufsbildung; Jugendlicher; Arbeitslosigkeit; Gegenmassnahme; Berufsbildung; Konzeption